2017
DOI: 10.1080/13554794.2017.1347264
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-brain connectivity in binge drinking college students: a diffusion tensor imaging study

Abstract: The current study used diffusion tensor imaging to examine patterns/degree of brain connectivity in 12 college-aged binge drinking (BD) and 12 moderate drinking individuals. Voxel-level and region-of-interest analyses revealed increased connectivity of the BD brain in the right corona radiata, right external capsule, and both the right and left cingulum. Also, fractional anisotropy and axial diffusivity values of these regions correlated with a number of drinking behaviors of the BD as well as both groups comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…FA, which quantifies the directionality of diffusion within a voxel between 0 (undirected, isotropic) and 1 (directed, anisotropic), is derived from the diffusion tensor and is the most commonly studied diffusion parameter of white matter microstructural properties related to the integrity of the fiber tract 21,22 . Increased (or decreased) FA in white matter tracts involved in cognitive processes is related to improved (or declined) cognitive function 7,23 , but the reduced FA in white matter tracts related to affective processes is related to increased severity of depression, anxiety or stress [24][25][26] . In the current study, the decreased FA on the bilateral C(cg) in CDs' may indicate increased severity of depression or anxiety (the C(cg) is responsible for pain, depression, mood, and anxiety perceptions 16,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…FA, which quantifies the directionality of diffusion within a voxel between 0 (undirected, isotropic) and 1 (directed, anisotropic), is derived from the diffusion tensor and is the most commonly studied diffusion parameter of white matter microstructural properties related to the integrity of the fiber tract 21,22 . Increased (or decreased) FA in white matter tracts involved in cognitive processes is related to improved (or declined) cognitive function 7,23 , but the reduced FA in white matter tracts related to affective processes is related to increased severity of depression, anxiety or stress [24][25][26] . In the current study, the decreased FA on the bilateral C(cg) in CDs' may indicate increased severity of depression or anxiety (the C(cg) is responsible for pain, depression, mood, and anxiety perceptions 16,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…All diffusion data were processed using the “Pipeline for Analyzing braiN Diffusion images” (PANDA): a toolbox implemented in MATLAB 1 ( Cui et al, 2013 ). This software employs several neuroimaging processing modules, namely, the FMRIB Software Library (FSL), the Pipeline System for Octave and Matlab (PSOM), the Diffusion Toolkit, and the MRIcron to automatically perform a series of steps (i.e., skull removal, correction of eddy current distortion, build diffusion tensor models) ( Cui et al, 2013 ; Kashfi et al, 2017 ; Hou et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The observed radial and mean diffusivity reduction can result from the extracellular matrix reorganization with increased tissue density [ 48 ]. Some studies have also reported a binge-drinking-associated increase in brain connectivity and FA of the cingulum (the area which is often associated with reward and positive reinforcement), in the corona radiata and capsula [ 60 62 ], or increase in the neurite density in the cortical white matter [ 63 ]. Such observed brain hyperconnectivity might place these individuals at higher risk of impulsive behavior, including binge drinking.…”
Section: Neuroimaging Neurocognitive and Neurophysiological Studmentioning
confidence: 99%